Immune Checkpoint Inhibitors in Peripheral T-Cell Lymphoma - Chen, Xi; Wu, Wanchun; Wei, Wenwen; Zou, Liqun (Frontiers in Pharmacology, 2022)
Peripheral T-cell lymphomas (PTCLs) are highly heterogeneous and present significant treatment challenges. Immune checkpoint therapies, such as PD-1 and CTLA-4 inhibitors, have significantly changed the clinical management paradigm of tumors. The roles of immune checkpoints in PTCL and related agents have been actively explored over recent years. PD-1 and PD-L1 expression is detectable in both PTCL and immune cells within the tumor microenvironment and forms the basis for the exploration of antibodies targeting these proteins. Such antibodies are currently being investigated in clinical trials to guide individualized therapy. PD-1/PD-L1 inhibitors alone and in combination with chemotherapy, radiotherapy, or targeted therapy have shown broad clinical efficacy and improved the survival of cancer patients. Studies of other immune checkpoint proteins, such as CTLA-4, TIM-3, LAG-3, and TIGIT, are likely to provide potential novel targets for immunotherapy. Here, we review the role of and recent advances in immune checkpoint blockade in common subtypes of PTCL, focusing on the anti-tumor immune responses to PD-1/PD-L1 blockers.